Trophic vulnerability of 0-group Atlantic cod (Gadus morhua) and saithe (Pollachius virens) : a case study investigating the juveniles' feeding pattern and identifying valuable nursery habitats in the Icelandic Westfjords - Nickel, Anja Katrin, 1988- (2016)
Verkefnið er lokað til 30.12.2017. Rapid environmental change due to anthropogenic impacts currently threaten marine ecosystems and increase the pressure on the vulnerable early life stages of many marine organisms. In this study I examine trophic vulnerability of 0-group Atlantic cod (Gadus morhua) and saithe (Pollachius virens) during late summer and fall. This period coincides with the Atlantic cod juvenile settlement from the pelagic to the benthic habitat in the northwest of Iceland. It is a critical period for both species as growth in the first summer and fall may determine winter survival. Results from previous studies have identified clear habitat preferences of juvenile gadoids for structured habitats such as maerl beds and macro-algae. In Iceland, both habitat types are exploited and affected directly and indirectly by anthropogenic activities. In the current study, I review prior literature to identify potential threats to nursery habitats of Atlantic cod and saithe, execute a case study to investigate the diets of 0-group cod and saithe juveniles and discuss the relevance of trophic preferences and trophic competition for nursery ground conservation and management. For the case study, samples were taken with a beach seine in shallow coastal waters, and the stomach contents of 146 0-group cod and saithe were qualitatively and quantitatively analyzed. Dietary composition showed that copepods constituted the main diet for both species. Further important prey organisms were cladocera, insects (Chironomidae), gastropoda, cyprid larvae, amphipoda and ostracoda. The feeding patterns of the 0-group juveniles revealed that both species are opportunistic feeders with a wide range of prey organisms. Despite that, there is high overlap in the foraging niche of cod and saithe, suggesting the potential for trophic competition between and within the two species. Juveniles of both species exhibited similar feeding patterns during most of the study time. During the sampling period from late July until November, ...